2018
DOI: 10.1177/1071100718762113
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Clinical Evaluation and Radiographic Hindfoot Alignment in Stage II Adult-Acquired Flatfoot Deformity

Abstract: Level II, prospective comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 40 publications
0
21
0
1
Order By: Relevance
“…17,35 This may suggest that the real alignment of the hindfoot may not be correctly assessed based on the conventional CR-CT sequence, particularly due to perspective distortion, which dramatically influences the value of the measured hindfoot alignment depending on the angle of rotation of the lower limb relative to the radiograph source, 3,5,41 and the absence of weightbearing in the case of conventional CT. It has also been shown that clinical evaluation of hindfoot alignment is not reliable 14 and that 2D evaluation through standard radiographs has poor reproducibility. 4,5,30 This might explain some cases of TAR implant failure where the alignment is thought to be correct but in fact is not in the 3D setting.…”
Section: Discussionmentioning
confidence: 99%
“…17,35 This may suggest that the real alignment of the hindfoot may not be correctly assessed based on the conventional CR-CT sequence, particularly due to perspective distortion, which dramatically influences the value of the measured hindfoot alignment depending on the angle of rotation of the lower limb relative to the radiograph source, 3,5,41 and the absence of weightbearing in the case of conventional CT. It has also been shown that clinical evaluation of hindfoot alignment is not reliable 14 and that 2D evaluation through standard radiographs has poor reproducibility. 4,5,30 This might explain some cases of TAR implant failure where the alignment is thought to be correct but in fact is not in the 3D setting.…”
Section: Discussionmentioning
confidence: 99%
“…Some feet may also exhibit a calcaneal valgus, but this is not always present with TTJ instability (18,19). Heel valgus occurs as a form of compensation from excessive internal talar rotation and plantar flexion (Figure 6) (20).…”
Section: Hindfoot Alignment and Biomechanicsmentioning
confidence: 99%
“…Weightbearing CT is an excellent modality for understanding complex 3-dimensional foot deformities including pes planovalgus and hallux valgus. 4,6,7,9,11,13 Lintz et al 16 demonstrated in a series of 135 feet that the FAO provides a highly reproducible means to measure hindfoot alignment with excellent inter- and intra-rater reliability. WBCT has also been shown to be more accurate than 2D imaging obtained via radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…The advent of this modality permits accurate assessment of complex foot deformity 3-dimensionally, such as pes planovalgus and hallux valgus. 4,[6][7][8][9]11,13,15 WBCT overcomes the well-documented operator and anatomical biases of previous modalities such as projection and rotation issues, 2,3,23 and standardized 3-dimensional biometrics have been validated to study hindfoot deformity. 16 WBCT has also been found to be more accurate than traditional CT for evaluation of the foot and ankle.…”
Section: Introductionmentioning
confidence: 99%